The Development Of Small Business And Private Entrepreneurship (Texas Journal of Multidisciplinary Studies, 2025)
This article analyzes the development and prospects of small business and private entrepreneurship. In the country's economy, small business and private entrepreneurship are a decisive factor in creating economic foundations for solving important development problems. They, possessing the greatest flexibility and adaptability to market demands, emerge as innovators in the lifestyle and living conditions of the population, showing the main path.